2001
DOI: 10.1099/0022-1317-50-3-284
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the antibacterial efficacy of several antiseptics tested on skin by an ‘ex-vivo’ test

Abstract: There are many skin antiseptics commercially available. Although their antibacterial activity has often been well studied [1], their potential effectiveness on skin remains poorly documented. To date, in-vivo protocols designed for the testing of the antimicrobial ef®cacy of antiseptics cannot use, for ethical reasons, pathogenic bacteria or new formulations whose toxicity in human subjects is unknown. An`ex-vivo' test was recently developed to overcome these problems. Freshly excised human skin from abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…Previous experiments validated the efficacy of these neutralizers to quench the activity of their respective antiseptics, and showed that they had no toxic effects on the test strain of Escherichia coli. 11 The in vivo tests were carried out with 12 female and three male volunteers (aged 18 -25 years). Participants had short fingernails and intact skin and were instructed not to apply antibacterial toiletries onto their forearms for 24 h before testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments validated the efficacy of these neutralizers to quench the activity of their respective antiseptics, and showed that they had no toxic effects on the test strain of Escherichia coli. 11 The in vivo tests were carried out with 12 female and three male volunteers (aged 18 -25 years). Participants had short fingernails and intact skin and were instructed not to apply antibacterial toiletries onto their forearms for 24 h before testing.…”
Section: Methodsmentioning
confidence: 99%
“…This ex vivo protocol was based on the method of Messager et al 11 Fresh samples of skin were obtained with patients' informed consent after plastic surgery (breast and abdominal reduction) and were cut to fit in diffusion cells (JB and DW Jones, Loughborough, UK) especially designed for that experiment with a donor compartment of 36 mm diameter. 11 The receptor compartment was filled with Earle's balanced salt solution (EBSS, Sigma, Poole, UK).…”
Section: Ex Vivo Protocol To Mimic the In Vivo Forearm Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the efficacy of a hygienic skin wash (HSW) and an alcoholic hygienic skin wash (AHSW) that both contained 5% TTO, as well as 5% TTO in Tween 80, was investigated in vivo according to the European handwashing test. 23 An ex-vivo test, which has been shown to be a reproducible potential substitute for in-vivo testing, [24][25][26] was adapted to imitate the handwashing technique and also used to assess the activity of TTO. Ex-vivo and in vivo data were compared.…”
Section: Introductionmentioning
confidence: 99%
“…The ex vivo antibacterial activity test was performed as previously described [Messager et al, 2001;Lboutounne et al, 2002]. Skin fragments were excised from abdominoplasties of female subjects obtained by surgical intervention.…”
Section: Evaluation Of the Ex Vivo Antibacterial Activitymentioning
confidence: 99%